Synthesis of new derivatives of 2-chloro-3-formyl-1,8-naphthyridine - Saleh, Mohanad Yakdhan; Ayoub, Ala Ismael (European Journal of Chemistry, 2014)
A simple and regioselective synthesis of 2-chloro-3-formyl-1,8-naphthyridine, through Vilsmeier-Haack cyclization of N-(pyridin-2-yl)acetamide has been reported. The reaction of 2-chloro-3-formyl-1,8-naphthyridine is also investigated and new series of 1,8-naphthyridine derivatives such as 3-chloro-4-(2-chloro-1,8-naphthyridine-3-yl)-1-(phenylamino)azetidin-2-one, 3-chloro-4-(2-chloro-1,8-naphthyridin-3yl)-1-((4-nitrophenyl) amino)-azetidin-2-one and 3-chloro-4-(2-chloro-1,8-naphthyridine-3-yl)-1-((2,4-dinitrophenyl) amino)-azetidin-2-one have been prepared. The formyl group in the 1,8-naphthyridine is subjected to further transformation into alkoxy carbonyl (NIS-K2CO3/alcohol) to afford 3-alkoxy carbonyl-1,8-naphthyridine and new hetero cyclic compounds such as oxadiazolo, thiadiazolo-thion and triazolo-thion have been prepared. The reaction between 2-chloro-3-formyl-1,8-naphthyridine and sodium sulphide in DMF produced 2-mercapto-3-formyl-1,8-naphthyridine. Some of the prepared compounds were found to have good biological activity against Staphylococcus aureus and Staphylococcus epidermidis.